Effects of pomegranate extract on preventing dental caries: a systematic review - Rafeie, Niyousha; Salimi, Yasaman; Aghamir, Zahra Sadat; Amini, Amirhesam; Taheri, Hamed; Sadreddini, Sarvin; Kamali, Fatemeh; Akbarian, Golnesa; Azizi, Nazanin; Bagherianlemraski, Mobina; Valizadeh, Maryam; Alimohammadi, Farnoosh; et al. (Frontiers in Oral Health, 2025)
Background/purposeThe present study aimed to evaluate the effect of pomegranate extract on the prevention of dental caries compared to standard care, placebo, and no intervention.Materials and methodsA bibliographic search in four databases, including PubMed, Scopus, Google Scholar, and CENTRAL, yielded 291 studies until September 8, 2023. The search was performed among the studies written in English using the search terms “Punica granatum” AND (“dental caries” OR “Streptococcus mutans” OR “tooth demineralization”) After screening the titles/abstracts and full texts of these studies, 7 articles were chosen.ResultsIn all 7 articles, pomegranate mouthwash was used as the intervention. In 5 studies, the control group used 0.2% chlorhexidine (CHX) mouthwash. Additionally, 4 articles reported a reduction in the mean Streptococcus mutans plaque count in both groups; however, better results were observed in the CHX mouthwash group. In one study, no significant difference was reported between the study and control groups. Finally, one study showed the significant superiority of a hydroalcoholic extract of pomegranate mouthwash over CHX mouthwash.ConclusionOverall, the results suggest that pomegranate extract mouthwash is highly effective in reducing caries-causing bacteria. No side effects were reported for pomegranate use in these studies.Systematic Review Registrationhttps://osf.io/69gpc/